2017
DOI: 10.1136/neurintsurg-2017-013063
|View full text |Cite
|
Sign up to set email alerts
|

Temporal cascade of inflammatory cytokines and cell-type populations in monocyte chemotactic protein-1 (MCP-1)-mediated aneurysm healing

Abstract: Background We have previously shown that monocyte chemotactic protein-1 (MCP-1) promotes aneurysm healing. Objective To determine the temporal cascade and durability of aneurysm healing. Methods Murine carotid aneurysms were treated with MCP-1-releasing or poly(lactic-co-glycolic) acid (PLGA)-only coils. Aneurysm healing was assessed by quantitative measurements of intraluminal tissue ingrowth on 5 μm sections by blinded observers. Results Aneurysm healing occurred in stages characteristic of normal woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…[88][89][90] Despite MCP-1 being generally described as a pro-inflammatory marker, several studies have also reported it to have a robust role in wound healing. [91][92][93] In contrast, RANTES, unlike MCP-1, is generally considered deleterious to the alternative noninflammatory roles of macrophages. 94,95 Therefore, its suppression appears to be desirable toward altering inflammatory polarization states.…”
Section: Discussionmentioning
confidence: 99%
“…[88][89][90] Despite MCP-1 being generally described as a pro-inflammatory marker, several studies have also reported it to have a robust role in wound healing. [91][92][93] In contrast, RANTES, unlike MCP-1, is generally considered deleterious to the alternative noninflammatory roles of macrophages. 94,95 Therefore, its suppression appears to be desirable toward altering inflammatory polarization states.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using MCP-1 KO mice in diabetic wound healing have shown reduced macrophage recruitment into the local environment ( 21 ). We have previously shown that recruitment of this macrophage axis is instrumental in our MCP-1 mediated aneurysm healing model ( 22 ). We have also previously shown that MCP-1 contributes to aneurysm healing by means of its downstream mediators ( 23 ).…”
Section: Discussionmentioning
confidence: 95%
“…As a first step in the healing process (Hoh et al, 2018), circulating neutrophils infiltrate the area containing Azan staining the hematoma. Then, monocytes and macrophages are recruited to the site of the hematoma to remove extracellular matrix debris by phagocytosis.…”
Section: Discussionmentioning
confidence: 99%